Evaluasi Pada Variasi Proses Bisnis Jenis Pembayaran Tagihan Air dengan Menerapkan Process Mining dan Quality Evaluation Framework (QEF) Pada Perusahaan Daerah Air Minum Kota Malang - Kartika Utami; Nanang Yudi Setiawan; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PDAM Malang City is one of Regional Owned Enterprises (BUMD) which provides clean water in Malang. As an organization in the service sector, PDAM Malang City is expected to give the best service for Malang's citizen in various business process viewpoint. A dominant service in PDAM is water payment which defined in three payment status based on an interview to resolve different customer characteristic. It is necessary to do an evaluation of the business process to guaranty best service in PDAM and understand business process quality which is currently running. The water payment business process is modeled by Yet Another Workflow Language (YAWL). Furthermore, the business process is simulated to acquire event log from the models. The event log is used to find business process variant using process mining method and ProM Tools. Evaluating the business process has been implemented by the Quality Evaluation Framework (QEF) method. There are 6 Quality Factors which doesn't suit with organization target. It shows that there are gaps between targets and performances in the organization. Further evaluation related to the business process variant so it can be concluded that the emergence of nonconformance in Quality Factor business process is not influenced by business process variant existence. And the existence of business process variant is not influenced by business process evaluation type of water payment in PDAM Malang City.